Peningkatan SDM Masyarakat Melalui Sadar Wisata di Desa Towale Kecamatan Banawa Tengah Kabupaten Donggala - Syamsul Bachri; Erwan Sastrawan Farid; Mohammad Zeylo Auriza; Rosida P Adam; Suardi Suardi (Yayasan Literasi Sains Indonesia, 2022)
The potential of marine tourism attraction owned by Towale Village is one of the tourist villages in the Donggala Regency, Central Sulawesi, which has now begun to attract a lot of tourists, especially marine tourism lovers. Problems in general are related to tourism, one of which is related to the quality of human resources, in this case the awareness of tourism by the community in tourist villages. Towale Village is one of the villages in Donggala Regency which will be designated as a Tourism Village. The low understanding of tourism awareness by the community is the reason why community service activities are carried out to increase human resources through tourism awareness in Towale Village, Central Banawa District. Donggala Regency. The method used in this service activity is the extension method by providing education and implementation examples aimed at tourism awareness. This activity was held in Towale Village in August by presenting 30 community leaders, village officials and tourism awareness groups. The results of this service provide an understanding to the community about how to grow tourism awareness in Towale Village, Banawa Tengah District, Donggala Regency.